Judges Analysis of Infographic Media Research Methodology - Sugihartini, Nyoman; Agustini, Ketut; Saindra Santyadiputra, Gede; Sintya Dewi, Kadek (Jurnal Pendidikan Indonesia, 2018)
This study aimed to design and implement the results of the video design of SOP Types - Types of Research for Lecture Research Methodology Based on Infographic Animation. The development of this video aimed to provide information about the Standard Operating Procedure (SOP) Research to all academics who are studying educational research methodology. The method used was research and development. The model used in building this technology was the ADDIE Model. The stages in the ADDIE model are Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). The final result of this project is in the form of an animated video containing several Standard Operating Procedure (SOP) that have been selected to create animated videos. This animated video can display animation in 2 dimensions. This animated video can also be used as a medium for delivering information to be more interesting. However, this article only discussed the results of expert test analysis, which includes: analysis of content experts and analysis media experts.